2006
DOI: 10.1146/annurev.immunol.24.021605.090535
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Perspective of Ctla-4 Function

Abstract: Within the paradigm of the two-signal model of lymphocyte activation, the interest in costimulation has witnessed a remarkable emergence in the past few years with the discovery of a large array of molecules that can serve this role, including some with an inhibitory function. Interest has been further enhanced by the realization of these molecules' potential as targets to modulate clinical immune responses. Although the therapeutic translation of mechanistic knowledge in costimulatory molecules has been relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
382
1
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 463 publications
(394 citation statements)
references
References 198 publications
7
382
1
4
Order By: Relevance
“…Increased levels of CTLA-4 are also characteristic of activated and memory T cells associated with downmodulation of CD28 4,29,30]. Almost all CTLA-4 1 T cells expressed CD28, but the level of CD28 expression in the CTLA-4 1 population in lupus T cells was significantly reduced compared with healthy controls (p 5 0.0001) (Fig.…”
Section: Ctla-4 Expression Is Significantly Increased In T Cells Frommentioning
confidence: 89%
See 1 more Smart Citation
“…Increased levels of CTLA-4 are also characteristic of activated and memory T cells associated with downmodulation of CD28 4,29,30]. Almost all CTLA-4 1 T cells expressed CD28, but the level of CD28 expression in the CTLA-4 1 population in lupus T cells was significantly reduced compared with healthy controls (p 5 0.0001) (Fig.…”
Section: Ctla-4 Expression Is Significantly Increased In T Cells Frommentioning
confidence: 89%
“…Several mechanisms have been proposed to explain the molecular basis for CTLA-4 inhibition including a dampening of T-cell signalling responses and alterations in T-cell motility [4,5]. The location and interaction of CTLA-4 within membrane lipid microdomains also influences its inhibitory function.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, CTLA-4 expression is increased by cAMP, suggesting a cAMPdependent regulation of CTLA-4 gene expression. 14 Significant increase of the CTLA-4 mutant alleles (À1722C, À1661G and À318T) and heterozygous genotypes (À1722 T/C, À1661 A/G and À318 C/T) in SSc patients rather than controls suggests that cytosine at position À1722, guanine at position À1661 and thymine at position À318 may affect the transcription level of the gene. In this regard, an association between CTLA-4 promoter genotypes at position À318 and levels of CTLA-4 molecule has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…mCTLA-4 upon binding to B7 molecules inhibits CD28/B7 interaction, resulting in downregulation of the immune response, 14 whereas increase in sCTLA-4 levels may block B7-mCTLA-4 interactions and thereby enhances T-cell activation and autoreactivity. In this regard, Sato et al 27 reported that increased levels of sCTLA-4 may be related to the abnormal immune response in SSc patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation